Analysis Of Students' Learning Motivation In DGMATH Based Problem-Based Learning On Number Operations Materials - Agus Prianggono; Dwi Ariani Finda Yuniarti (STKIP Singkawang, 2023)
Mathematics is a basic subject that is important to master. Since the 2019 covid pandemic, student learning at the elementary school level has been neglected. Online learning is an alternative, but student learning outcomes are still not optimal. Student motivation needs to get attention, because student learning motivation is a driving force for enthusiasm and student interest in learning. The purpose of this study is to provide quantitative calculation results and describe the calculation results for each indicator of student learning motivation using the Project Based Learning (PBL) model based on the DGMATH application in mathematics learning, especially material on number operations for low grade elementary school students. The method of this research is to use quantitative methods, where the research sample is 56 students with the sample selection technique is random sampling technique. The results showed that DGMATH-based Project Based Learning (PBL) learning had an average level of learning motivation of 85.90%, where the results consisted of seven indicators the result was 81.96% on the first indicator which means that almost all students are interested in participating in activities learning mathematics, for the second indicator that is independence in doing math tasks is 85.42%, the third indicator is the frequency in learning mathematics is 89.29%, the fourth indicator is 82.14% which means that almost all students have the urge to learn and high achievement, while the fifth indicator is 87.95% which means that almost all have persistence in doing assignments and participating in mathematics learning, for the sixth indicator is 83.93% where almost all students have high self-confidence in participating in mathematics learning and indicators Finally, the level of discipline in following defenders math jargon of 90.63%. So it can be concluded that almost all students have high motivation in participating in DGMATH-based PBL learning activities.